The Ontology of Biological Groups: Do Grasshoppers Form Assemblages, Communities, Guilds, Populations, or Something Else? - Jeffrey A. Lockwood (Psyche: A Journal of Entomology)
Acridologists have used a variety of terms to describe groups of grasshoppers, including assemblage, community, guild, and population. This terminological diversity has raised the question of whether one of these descriptors is the correct one. I take the position that these terms pick out different features of the natural world such that there is no unconditionally or uniquely correct term. By adopting the framework of constrained perspectivism—a form of philosophical pragmatism—it is argued that a term is correct if it accurately reflects the conceptual framework of the investigator and effectively communicates this perspective to others. Such an approach gives rise to terminological pluralism that avoids the problems of relativism (the subjectivist's view that any term can be used) and absolutism (the objectivist's view that there is a single correct term). I describe the contexts in which the most common terms are appropriate.